Relationship and structural diversity of bacterial manganese superoxide dismutases and the strategy for its application in therapy and cosmetics - Debbie S. Retnoningrum; Aluicia Anita Artarini; Wangsa T. Ismaya; Abykhair Muhammad; Muhammad D. Fadilah; Ratna A. Utami (Microbiology Indonesia, 2021)
Manganese superoxide dismutase (MnSOD) from bacteria shares high amino acid sequence homology and nearly identical structure. Despite of that, their characteristics are diverse, which likely due to their bacterial origin and adaptation to the environment. Most importantly, their structural similarity extends to eukaryotic MnSOD, i.e. human. Therefore, structural study of bacterial MnSOD is relevant to its human SOD and henceforth for its use in human as a therapeutic agent or a cosmetic ingredient. Further, eukaryotic MnSOD occurs as a tetramer while almost all of the prokaryotic are dimeric. In this review, relationship between the amino acid sequences and structures of MnSOD as well as their origin and evolution is discussed. The structures of FeSOD and cambialistic SOD, which are MnSOD closest homologs, are visited as the comparison. This study provides an insight to potential safe application of bacterial MnSOD, including necessary modifications to obtain desired characteristics for applications in human.